Explicit relations for the reduced module and harmonic measure - Bely, V. I.; Kravchuk, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Exact relations are established for the reduced modules of the families of curves separating certain connected subsets in arbitrary connected domains. New explicit expressions for the harmonic measure of a connected boundary subset are obtained as corollaries.